The lowest-metallicity type II supernova from the highest-mass red supergiant progenitor. (July 2018) - Anderson, J.; Dessart, L.; Gutiérrez, C.; Krühler, T.; Galbany, L.; Jerkstrand, A.; Smartt, S.; Contreras, C.; Morrell, N.; Phillips, M.; Stritzinger, M.; Hsiao, E.; et al.
Abstract Red supergiants have been confirmed as the progenitor stars of the majority of hydrogen-rich type II supernovae1 . However, while such stars are observed with masses >25 M ⊙ (ref.2 ), detections of >18 M ⊙ progenitors remain elusive1 . Red supergiants are also expected to form at all metallicities, but discoveries of explosions from low-metallicity progenitors are scarce. Here, we report observations of the type II supernova, SN 2015bs, for which we infer a progenitor metallicity of ≤0.1 Z ⊙ from comparison to photospheric-phase spectral models3, and a zero-age main-sequence mass of 17–25 M ⊙ through comparison to nebular-phase spectral models4, 5 . SN 2015bs displays a normal 'plateau' light-curve morphology, and typical spectral properties, implying a red supergiant progenitor. This is the first example of such a high-mass progenitor for a 'normal' type II supernova, suggesting a link between high-mass red supergiant explosions and low-metallicity progenitors. Supernova SN 2015bs is a hydrogen-rich type II supernova that appears to have been generated by a high-mass (>18 M ⊙ ) and low-metallicity (<0.1 Z ⊙ ) red supergiant progenitor.